Matrix Metalloproteinases in Invertebrates - Liu, Xi; Liu, Dongwu; Shen, Yangyang; Huang, Mujie; Gao, Lili; Zhang, Zonghan; Liu, Baohua; Zhao, Bosheng; Pang, Qiuxiang (Protein and Peptide Letters, 2020)
Matrix Metalloproteinases (MMPs) belong to a family of metal-dependent endopeptidases which contain a series of conserved pro-peptide domains and catalytic domains. MMPs have been widely found in plants, animals, and microorganisms. MMPs are involved in regulating numerous physiological processes, pathological processes, and immune responses. In addition, MMPs play a key role in disease occurrence, including tumors, cardiovascular diseases, and other diseases. Compared with invertebrate MMPs, vertebrate MMPs have diverse subtypes and complex functions. Therefore, it is difficult to study the function of MMPs in vertebrates. However, it is relatively easy to study invertebrate MMPs because there are fewer subtypes of MMPs in invertebrates. In the present review, the structure and function of MMPs in invertebrates were summarized, which will provide a theoretical basis for investigating the regulatory mechanism of MMPs in invertebrates.
Keywords: structure